(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The child must have initiative and independence in various types of children’s activities, the ability to choose occupations, partners, to generate and implement various plans, be confident in their abilities and open to the outside world. Therefore, the use of technology in organizing the developmental educational space of a preschooler is stimulating the child’s communicative, playful, cognitive, physical and other types of activity, which contributes to his physical, psychological and intellectual development.